2020
DOI: 10.1074/jbc.ra120.013280
|View full text |Cite
|
Sign up to set email alerts
|

The viral protein U (Vpu)-interacting host protein ATP6V0C down-regulates cell-surface expression of tetherin and thereby contributes to HIV-1 release

Abstract: Host proteins with antiviral activity have evolved as first-line defenses to suppress viral replication. The HIV-1 accessory protein viral protein U (Vpu) enhances release of the virus from host cells by down-regulating the cell-surface expression of the host restriction factor tetherin. However, the exact mechanism of Vpu-mediated suppression of antiviral host responses is unclear. To further understand the role of host proteins in Vpu's function, here we carried out yeast two-hybrid screening and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Other retroviruses, like HIV-1 or -2 or human T-cell leukemia virus type 1 (HTLV-1) or 2, enter the cells pH independently, indicating that vacuolar ATPase is not required for HIV or HTLV entry ( McClure et al, 1988 ; Stein et al, 1987 ). Interestingly, a recent report has suggested that the V o subunit C of the vacuolar ATPase, which forms the proton transporting channel, plays a role in regulating tetherin expression and therefore regulates the assembly and release of HIV ( Waheed et al, 2020 ). Thus, it seems that apart from its role in viral entry by lysosomal acidification, the vacuolar ATPase is also important for the release of newly synthesized virions.…”
Section: Discussionmentioning
confidence: 99%
“…Other retroviruses, like HIV-1 or -2 or human T-cell leukemia virus type 1 (HTLV-1) or 2, enter the cells pH independently, indicating that vacuolar ATPase is not required for HIV or HTLV entry ( McClure et al, 1988 ; Stein et al, 1987 ). Interestingly, a recent report has suggested that the V o subunit C of the vacuolar ATPase, which forms the proton transporting channel, plays a role in regulating tetherin expression and therefore regulates the assembly and release of HIV ( Waheed et al, 2020 ). Thus, it seems that apart from its role in viral entry by lysosomal acidification, the vacuolar ATPase is also important for the release of newly synthesized virions.…”
Section: Discussionmentioning
confidence: 99%
“…By degrading tetherin, Vpu enhances the release of viral particles from infected cells [100,101]. However, recent studies have shown that tetherin also plays a role in the transport of MHC I molecules to the cell surface [102]. Tetherin interacts with newly synthesized MHC I molecules and promotes their transport to the cell surface, where they can present viral antigens to the immune system [103].…”
Section: Downregulation Of Mhc Class I and Iimentioning
confidence: 99%
“…For example, tetherin has been shown to interact with autophagy via multiple different pathways. In the context of HIV-1 infection, HIV-1 Vpu has been reported to downregulate tetherin expression on the cell surface by promoting its ubiquitination and subsequent intracellular sequestration and/or degradation within autophagosomes or lysosomes, thus potentially hijacking the autophagy pathway for the benefit of the virus [ 188 , 189 ]. Strikingly, breast cancer-associated gene 2 (BCA2, also known as Rabring7, ZNF364, or RNF115), a RING-type E3 ubiquitin ligase, was shown to interact with tetherin to promote HIV-1 packaging into CD63 + endosomes, with the end result being lysosomal degradation of HIV-1 virions and tetherin in a manner reminiscent of tetherin-dependent autophagic degradation of damaged mitochondria in uninfected cells [ 190 , 191 ].…”
Section: Hiv-1 Escapes Hutrim5α-mediated Restriction In Submucosalmentioning
confidence: 99%